PUBLIC-PRIVATE AND CIVIL SOCIETY PARTNERSHIP IN CULTURAL HERITAGE MANAGEMENT IN THE CASE OF ARCHAEOLOGICAL SITES: THAILAND’S REGULATIONS, POLICIES, IMPLEMENTATION, AND LIMITATION - Ratchaphon Amsuk (PEOPLE: International Journal of Social Sciences, 2025)
The public-private partnership is a principal approach utilized and favored in public administration throughout numerous countries. Nevertheless, management in the public sector encompasses not only the distinction between the private and public sectors but also includes civil society. This article seeks to illustrate the public-private and civil society partnerships in cultural heritage management concerning archeological sites in Thailand, focusing on regulations, policies, implementation, and limitations. The qualitative approach was employed to gather data. The findings indicated that no regulation, law, or policy specifically deals with public-private partnerships, particularly in the management of cultural heritage concerning archaeological sites and civil society participation. Instead, these are managed by a combined set of other laws and regulations, like the Cultural Heritage Act and the Public-Private Partnership Act. From the implementation perspective, each government agency utilizes its policies to support project execution in alignment with the executive vision of private initiatives. The absence of explicit laws and regulations limits public-private and civil society partnerships in cultural heritage management, specifically regarding archaeological sites in Thailand. To enhance cultural heritage management for archaeological sites, it is crucial to establish clear laws and regulations and engage all sectors, particularly the public sector, which truly owns the state asset, in understanding its implementations. The project must address the business benefits for investors, conservation considerations, and public engagement to prevent conflicts and enhance community understanding of heritage management for both business and preservation purposes.